Lumbar spondylolysis: tactical approaches, indications and types of surgical interventions, treatment results. A systematic review - A.V. Evsyukov; O.G. Prudnikova; E.A. Matveev; M.S. Strebkova (Хирургия позвоночника)
Objective. To analyze the literature data on treatment tactics for patients with spondylolysis of the lumbar vertebrae, and to determine indications for surgical treatment, types of surgical interventions, criteria for assessing treatment results, complications and rehabilitation after treatment. Material and Methods. Full text articles were selected from the Pubmed, EMBASE, eLibrary, Google and Yandex databases. The type of articles was a systematic review and meta-analysis, and the search period was 10 years. The literature search was carried out by three researchers. The study was conducted in accordance with the international PRISMA guidelines for writing systematic reviews and metaanalyses. The levels of evidence reliability and gradation of strength of recommendations were assessed according to the ASCO protocol. Results. A total of 6812 articles on the topic under consideration were found, of them 4922 articles with full text, 2155 over the past 10 years, 115 systematic reviews and meta-analyses. Fourteen articles met the inclusion criteria. Conclusion. Indications for surgical treatment of spondylolysis are the failure of conservative treatment for 6 months, worsening of clinical symptoms, and development of spondylolisthesis. The goal of the surgery is bone fusion formation at the level of the defect, restoration of spinal stability and preservation of mobility of the corresponding segment. Surgical treatment methods for spondylolysis using transpedicular screws and a beam (Gillet) showed a higher fusion result than the Scott and Morscher methods. Minimally invasive methods (Buck method and its modifications) provide better functional results. The highest complication rate is observed in surgical interventions using the Scott method (wire rupture, transverse process fracture, lack of fusion) and those using the Morscher method (superficial infection, instability of implants and persistent back pain). The choice of surgical method should be based on the surgeon’s preferences and experience.